The evolution of industry in Uganda - Marios Obwona; Isaac Shinyekwa; Julius Kiiza; Eria Hisali (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
The paper looks at the evolution of industry in Uganda examining drivers and constraints since the pre-colonial period in the 1940s to date. It is argued that the state played a central role in industrialization during the pre-colonial and immediate post-colonial period. The paper further looks at industrialisation during the liberal phase. The current structure, size and distribution of industry are discussed in light of the laissez fair paradigm. The non-direct interventionist policy to industrialization has not been adequate to propel industrial development in Uganda. State withdrawal from direct involvement in industrial development was prematurely done and should be revisited
Keywords: B15; B52; L11; L16; 330; industry; structure; firm; evolution; size; distribution; policy